Bibliometric and Visual Analysis of Elbow Tendinosis Research in Orthopaedic Surgery - Alaaddin Üzümcügil (Genel Tıp Dergisi)
Aim: Elbow tendinosis is the most frequent cause of elbow discomfort. The disease is common in the daily routine practice of sports medicine and orthopedics. However, currently, this issue lacks a multifaceted, methodical, and understandable visual examination. Materials and Methods: Utilizing the Biblioshiny program, the core collection dataset of the Web of Science database's literature on elbow tendinosis from 1970 to April 2023 was compiled and examined. Research hotspots and development patterns were examined in terms of highly influential authors, research institutions, nations or regions, keywords, and referenced publications. Results: According to the search criteria, 526 articles were published by 1817 authors from 839 affiliations, and 47 countries in the Web of Science database. The amount of articles on elbow tendinosis has increased over time, especially after 2000. 55.6% of all articles were published in 2010 and later years. The articles included in this study were published in the United States (n=152, 28.843%), England (n=43, 8.159%), Germany (n=40, 7.59%), Turkey (n= 40, 7.59%) and South Korea (n=28, 5.313%). The United States had the highest total citation number 4493, but Canadian publications had the highest number of average article citations (56.4). Conclusion: Although studies on elbow tendinosis in the field of orthopedics have gained momentum in recent years, they are still insufficient. Although the United States ranks first in terms of publications, it is pleasing for our country that Turkey ranks high.